Importance of thorough tissue and cellular level characterization of targeted drugs in the evaluation of pharmacodynamic effects. - Dustin K Bauknight; Victoria Osinski; Siva Sai Krishna Dasa; Anh T Nguyen; Melissa A Marshall; Julia Hartman; Matthew Harms; Gavin O'Mahony; Jeremie Boucher; Alexander L Klibanov; Coleen A McNamara; Kimberly A Kelly (PLoS ONE, 2019)
Targeted nanoparticle delivery is a promising strategy for increasing efficacy and limiting side effects of therapeutics. When designing a targeted liposomal formulation, the in vivo biodistribution of the particles must be characterized to determine the value of the targeting approach. Peroxisome proliferator-activated receptor (PPAR) agonists effectively treat metabolic syndrome by decreasing dyslipidemia and insulin resistance but side effects have limited their use, making them a class of compounds that could benefit from targeted liposomal delivery. The adipose targeting sequence peptide (ATS) could fit this role, as it has been shown to bind to adipose tissue endothelium and induce weight loss when delivered conjugated to a pro-apoptotic peptide. To date, however, a full assessment of ATS in vivo biodistribution has not been reported, leaving important unanswered questions regarding the exact mechanisms whereby ATS targeting enhances therapeutic efficacy. We designed this study to evaluate the biodistribution of ATS-conjugated liposomes loaded with the PPARα/γ dual agonist tesaglitazar in leptin-deficient ob/ob mice. The ATS-liposome biodistribution in adipose tissue and other organs was examined at the cellular and tissue level using microscopy, flow cytometry, and fluorescent molecular tomography. Changes in metabolic parameters and gene expression were measured by target and off-target tissue responses to the treatment. Unexpectedly, ATS targeting did not increase liposomal uptake in adipose relative to other tissues, but did increase uptake in the kidneys. Targeting also did not significantly alter metabolic parameters. Analysis of the liposome cellular distribution in the stromal vascular fraction with flow cytometry revealed high uptake by multiple cell types. Our findings highlight the need for thorough study of in vivo biodistribution when evaluating a targeted therapy.